Financial Management Based on Justice in Achieving Accountability at Nene' Mallomo Hospital, Sidrap Regency - Rahyuni, Gusty; Majid, Jamaluddin; Jannah, Raodahtul (Phinisi Applied Accounting Journal, 2024)
The purpose of this study was to determine the financial management and accountability at Nene' Mallomo Hospital, Sidrap Regency based on the concept of justice. Financial management is defined as a series of activities that include planning, budgeting, implementation, administration, reporting, accountability, and supervision of financial management. This study was conducted at Nene' Mallomo Hospital located in Pangkajene, Sidrap Regency, South Sulawesi. The sample in this study were the head of the hospital UPT, head of the financial sub-section, nurses, hospital staff, patients, and the related community. Data collection methods were through observation, interviews, documentation, literature studies and internet searching. The results of this study indicate that Nene' Mallomo Hospital, Sidrap Regency has fulfilled the principles of accountability and good governance in its financial management, in accordance with the objectives and applicable laws and regulations. Accountability and transparency in financial management or financial reports are important because they are a form of information conveyed to the government or the community regarding the funds managed whether they are in accordance with the allocation and place. Nene' Mallomo Hospital instills the values of justice in its service to the community and its financial management. Providing several payment programs for patients and providing good performance to all groups of patients. The implications of this study are to inform what insurance programs are accepted at Nene' Mallomo Hospital and also to provide tools or tests to evaluate public satisfaction. Tujuan dari penelitian ini adalah untuk mengetahui pengelolaan keuangan dan akuntabilitas di Rumah Sakit Nene' Mallomo, Kabupaten Sidrap berdasarkan konsep keadilan. Pengelolaan keuangan didefinisikan sebagai serangkaian aktivitas yang meliputi perencanaan, penganggaran, pelaksanaan, administrasi, pelaporan, akuntabilitas, dan pengawasan terhadap pengelolaan keuangan. Penelitian ini dilakukan di Rumah Sakit Nene' Mallomo yang terletak di Pangkajene, Kabupaten Sidrap, Sulawesi Selatan. Sampel dalam penelitian ini adalah kepala UPT rumah sakit, kepala sub-bagian keuangan, perawat, staf rumah sakit, pasien, dan masyarakat terkait. Metode pengumpulan data dilakukan melalui observasi, wawancara, dokumentasi, studi pustaka, dan pencarian internet. Hasil penelitian ini menunjukkan bahwa Rumah Sakit Nene' Mallomo, Kabupaten Sidrap telah memenuhi prinsip akuntabilitas dan tata kelola yang baik dalam pengelolaan keuangannya, sesuai dengan tujuan dan peraturan perundang-undangan yang berlaku. Akuntabilitas dan transparansi dalam pengelolaan keuangan atau laporan keuangan sangat penting karena merupakan bentuk informasi yang disampaikan kepada pemerintah atau masyarakat terkait dana yang dikelola, apakah sesuai dengan alokasi dan tempatnya. Rumah Sakit Nene' Mallomo menanamkan nilai-nilai keadilan dalam pelayanannya kepada masyarakat dan dalam pengelolaan keuangannya. Menyediakan beberapa program pembayaran bagi pasien dan memberikan kinerja yang baik kepada semua kelompok pasien. Implikasi dari penelitian ini adalah untuk memberi informasi mengenai program asuransi yang diterima di Rumah Sakit Nene' Mallomo dan juga memberikan alat atau uji untuk mengevaluasi kepuasan masyarakat.